Understanding trends in electrochemical carbon dioxide reduction rates - Xinyan Liu (Nature Portfolio, 2017)
Identifying trends in electrocatalytic activity for carbon dioxide reduction can help with catalyst design, but are difficult to define. Here, the authors develop an electrochemical kinetic model of the process, identifying scaling relations relating transition state energies to CO adsorption energy on metal surfaces.